Sports Journalism's Uncertain Future: Navigating the Current Media Ecosystem in the Wake of the COVID-19 Pandemic. (27th July 2022) - Gentile, Patrick C.; Buzzelli, Nicholas R.; Sadri, Sean R.; Arth, Zachary W.
ABSTRACT: In March 2020, the sporting landscape was paused indefinitely due to the COVID-19 pandemic. To understand how the job function and routines of newspaper sports journalists were impacted during the initial U.S. outbreak (March to July 2020), semi-structured in-depth interviews with 23 members of United States (US) print sports media were conducted. Interviewee responses elucidated three main themes: the future of sports journalism is unknown and frightening for those working in the industry, COVID-19 illustrates the importance of interpersonal relationships to produce quality stories, and COVID-19 validates the importance of quality sports journalism. Additionally, interviewees also shed light on the impact that videoconference interviews, specifically those conducted over Zoom, have on the sports journalism field. Even though it was deemed a useful tool during the pandemic, sportswriters feared that teams will continue to limit access by relegating all interviews to Zoom, thus drastically changing the norms of sports journalism. The theoretical implications of these findings are discussed.